PERAN SENI MUSIK DALAM DUNIA PENDIDIKAN DI TNGKAT SEKOLAH DASAR - Asriana Harahap (Pendidikan Guru Madrasah Ibtidaiyah Institut Agama Islam Negeri Padangsidimpuan, 2023)
Music is a body-based artistic expression. The music consists of loops or feedback or feedback hide, listen and hide again. Making music is equivalent to talking to the body. The art of music has a vital role in various levels of society, considering that music is a very effective medium as an entertainer and messenger. The method used in this study is library research with the type of Systematic Literature Review (SLR), where researchers want to systematically and in-depth compile empirical evidence that has been found and published by previous researchers to be used to provide a complete interpretation of the research results. The art of music is an expression through the sound and rhythm of a tone. The function of the art of music is to build creativity that contains the value of harmony and discipline in the form of notes that have a good deal. In addition, Music Arts discusses how musical notes are made and different types of music, such as vocal and instrumental. Looking at this concept of music gives us a more general understanding of music, and the art of music is a work of art. At a low level of human civilization, the art of music is used in almost all aspects of life.